Development of Basic English Grammar Teaching Materials Based on Situational Approach in English Language Education Study Program of Universitas Muslim Indonesia - Muhammad Yunus; Abdollah Abdollah; Andi Hudriati (Universitas Negeri Makassar, 2020)
This study is a research development of Basic English Grammar teaching materials in the English Language Education Study Program of the Faculty of Literature UMI. This study aims to obtain more effective teaching methods between Oral Approach and Teacher Center Learning or lecture methods. This research was conducted using the pseudo experiment method (quasi experimental research). Quasi Experimental Design in this design was used by two groups of subjects. One group was given a specific treatment (experiment), while the other was used as a control group. Both groups were given pre-test measurements. After that the group given treatment (Situational Based Approach) is an experimental group, then both groups are done measurement (post-test) or acquisition. Pre-test Group - Treatment - Post-test. Research site at UMI Faculty of Literature. The number of respondents as many as 50 students is divided into two groups, namely the experiment group and the control group of 25 people each. The results showed that there was a significant difference between the Oral Approach method and the Teacher Center Learning method or the lecture method in improving the student's learning outcomes in Basic English Grammar learning. The cause is that the Oral Approach method has a higher average and improvement compared to the Teacher Center Learning method or lecture method because the Oral Approach method brings more active students into learning. Although given the same material at the same time, but in oral approach method therefore students are active in the learning process. So, lecturers are just facilitators. While in the method of lecture students are only fixated on the explanation of teachers and students are less active in learning. Therefore, oral approach teaching method is more effective than Teacher Center Learning method on Basic English Grammar teaching.